Sustainable approach to waste management in sri lanka- municipal solid waste composting – conceptual paper - Herath, H.M.I.S.K. (Faculty of Management Studies and Commerce, University of Jaffna, Sri Lanka, 2019)
Municipal Solid Waste Management is a major component of sustainable production and consumption. Municipal Solid Waste is defined as any discarded or abandoned materials arising from domestic, commercial, industrial, and institutional activities in urban areas. The Municipal Solid Waste Management (MSWM) is a process of waste disposal in a way that reduces or eliminates adverse effects on the environment ,human health and supports economic growth while improving the quality of life and providing a sustainable environment for the future. Reduce reuse recycle recover and disposal are desirable options which can be practiced to minimize the amount of MSW in Sri Lanka. The aim of this study is to discuss the main practices under recycling in Sri Lankan context : mainly composting of MSW. Hence composting is one of the effective method which can be used in both reducing waste as well as increasing agricultural sustainability. Identifying the socio economic factors which affect for the use of compost produced from Municipal Solid Waste(MSW) in agriculture, identifying their potentials and constraints associated with use of compost and propose ways and means to promote MSW compost among communities. This paper is based on secondary data as an inductive analysis in relation to Municipal Solid Waste Management in Sri Lanka. Secondary data were collected from published sources. Accordingly this paper represents a brief on sustainable approach to waste management by Municipal Solid waste composting in Sri Lanka.
Keywords: Sustainability; Municipal Solid Waste; Compost